2018
DOI: 10.1016/j.ecolecon.2018.05.006
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Climate Change Adaptation Alternatives for Smallholder Farmers in the Upper Blue-Nile Basin

Abstract: Climate change is expected to have severe negative impacts on the livelihoods of smallholder farmers in developing countries. However, smallholder farmers and governments in these regions tend to be ill-prepared for the impacts of climate change. We present the results of a stakeholderbased multi-criteria analysis of climate change adaptation options for agriculture, natural resource management and water management in the upper Blue-Nile basin in Ethiopia. We use the PROMETHEE II outranking method to analyse d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 37 publications
0
14
0
1
Order By: Relevance
“…Similarly, Bedeke et al (2018) showed that in the face of climate change, drought-resistant-improved seed, along with chemical fertilizer, increases farm productivity and net economic returns. Improved seed is justified by farmers as the preferred option among the list of agricultural adaptation practices in the upper Blue Nile basin (Nigussie et al 2018). Similarly, Di Falco, Veronesi, and Yesuf (2011) found that seed is significantly associated with the increase in yield for those adapters, while labor and fertilizer for non-adapters.…”
Section: Determinants Of Crop Yieldmentioning
confidence: 98%
See 1 more Smart Citation
“…Similarly, Bedeke et al (2018) showed that in the face of climate change, drought-resistant-improved seed, along with chemical fertilizer, increases farm productivity and net economic returns. Improved seed is justified by farmers as the preferred option among the list of agricultural adaptation practices in the upper Blue Nile basin (Nigussie et al 2018). Similarly, Di Falco, Veronesi, and Yesuf (2011) found that seed is significantly associated with the increase in yield for those adapters, while labor and fertilizer for non-adapters.…”
Section: Determinants Of Crop Yieldmentioning
confidence: 98%
“…One of the ways out of these challenges is the enforcement of adaptation strategies that substantially minimize current and future climate change and contribute to food security (Di Falco and Veronesi 2018;Khanal et al 2018). The most commonly cited climate change adaptation strategies include adjustment of planting and harvesting time, diversification, improved crop variety, adoption of soil and water conservation practices (SWC), irrigation, agroforestry, planting trees, development of early warning system and so forth (Deressa et al 2009;Di Falco 2014;Mengistu, Bewket, and Lal 2015;Amare and Simane 2018;Antwi-Agyei et al 2018;Khanal et al 2018; Komba and Muchapondwa 2018;Nigussie et al 2018;Teklewold, Mekonnen, and Kohlin 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Drip irrigation works well in arid and semi-arid areas. It has not only high water-supply efficiency but also nutrients can be supplied through this system, reducing risks of leaching or volatilization (Nigussie et al 2018).…”
Section: Drip Irrigation Systemmentioning
confidence: 99%
“…They took into account not only technical criteria from the operations research field but also the specificities related to the application domain; basic features allowing for incommensurability, non-compensation and incomparability are adequately fulfilled by outranking methods. In the context of decision on crop selection by farmers, outranking methods have been applied by various authors in different contexts [3][4][5][6][7]. However, the number and the scope of applications is rather limited; especially where policy-making support is concerned, such models are mainly used to select and rank alternatives and not to evaluate policy measures and/or quantitatively determine support to farmers to implement the chosen alternative.…”
Section: Introductionmentioning
confidence: 99%